Gloss on the judgement of the Supreme Court of 28 February 2023, I KZP 13/22 (expressing approval) (Ius Novum, 2023)
The present gloss refers to the thesis and considerations expressed in the Supreme Court judgement of 28 February 2023, I KZP 13/22, concerning the exception to the rule of speciality stipulated in Article 14(1)(b) of the European Convention on Extradition. The author presents arguments concerning the broad international legal context of the analysed regulation, which develops and confirms the accuracy of the Supreme Court’s stance on a broader than lexical interpretation of the term ‘final discharge’. Moreover, the paper discusses the nature of the exception in question in the light of the standard of protection laid down in Article 52(4) of the Constitution of the Republic of Poland.